DESIGN FOR ADAPTABILITY AND DISASSEMBLY:: A REVIEW TO ACHIEVE BUILDINGS’ DECONSTRUCTION - MUNARO, Mayara Regina; TAVARES, Sergio Fernando (Encontro Latino-americano e Europeu sobre Edificações e Comunidades Sustentáveis (euroELECS), 2023)
Reusing and recycling building materials and components are an alternative to minimizing construction and demolition waste (CDW). The introduction of ecodesign methodologies in the design stage enables buildings to be adapted to the needs of users and deconstructed at the end-of-life. Design for Adaptability and Disassembly (DfAD) is a method that incorporates sustainable principles and brings environmental, social, and economic benefits to the construction sector. Although, seeks to maintain materials at their highest level of utility and value, supporting the implementation of the circular economy (CE) principles, is little explored in projects and constructions. This study analyses how the construction sector approaches the DfAD to achieve buildings’ deconstruction. Through an integrative literature review, 279 articles were selected and categorically analyzed. The results show the concentration of the studies in three major categories: i) design and planning process; (ii) buildings’ end-of-life; and (iii) circular assessments and strategic values, and a framework was proposed. The framework outlines the main circular strategies found in the literature that make it possible to deconstruct and recover components, products, and materials at the end of the building’s life. This framework can be used as guidance for academics, professionals, and decision-makers to expand knowledge about the potential applications of the DfAD method. The need for more explanations and knowledge on DfAD, on deconstruction strategies, on reusing of materials and components, and on the life cycle tools as decision support at the material end-of-life is crucial to make buildings resilient and adaptable.